FACE ACCUPRESSURE TREATMENT IN REDUCE THE LEVEL OF ANXIETY FOR POSTPARTUM MOTHERS: FACE ACCUPRESSURE TREATMENT IN REDUCE THE LEVEL OF ANXIETY FOR POSTPARTUM MOTHERS - Pardede, Desika Wali (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2022)
Childbirth was a natural process bestowed by God on a woman. After giving birth, many people think that pregnancy was a woman's nature that must go through, but in reality, a woman who gives birth could be a dramatic and traumatic episode that really determines her life, because a mother who experiences stress, feelings of sadness and fear will affect the mother's emotional and sensitivity during the postpartum period. Anxiety was an emotional condition as a warning sign of a person's physical condition against the occurrence of a problem. Therapy that could overcome anxiety by stimulating the release of endorphins (hormones of happiness). Several therapies were applied to stimulate the release of endorphins, including massage therapy. Face acupressure is one of the complementary therapies for dealing with anxiety because it was a type of acupressure (massage by pressing acupuncture points. Face acupressure was done by applying pressure with the fingertips on acupuncture points on the face which aimed to help expedite the flow of energy in the body, regulate blood flow and movement of lymph, increase immunity, make the body more relaxed and clear the mind as well as soften the skin. The implementation of this activity WAS expected to increase the ability of midwives to reduce the anxiety of postpartum mothers.